Day-Ahead Optimal Interval Scheduling for Building Energy System Considering Building Envelope Virtual Energy Storage Uncertainties - Mu, Yunfei; Zhang, Yaqing; Liu, Zhe; Gao, Yi; Deng, Youjun; Jin, Xiaolong; Jia, Hongjie; Zhang, Jiarui (Frontiers in Energy Research, 2022)
The heat storage property of building envelope is usually modeled into a virtual energy storage (VES), and regarded as a flexibility resource to support the energy scheduling of building energy system (BES). However, the adjustable potential of the VES is uncertain incurred by several ambient random variables with/without specific probability distributions, posing challenges on determining the operational planning schemes of the BES. This paper is intended to study a day-ahead optimal scheduling method for PV-integrated BES (known as PV-BES) with the consideration of the VES using interval optimization methods. Firstly, interval number is used to characterize the uncertainties of outdoor temperature, light irradiance and the occupant’s behavior reflected by the uncontrollable household load. Secondly, an interval VES model is developed by modelling VES’s virtual charge-discharge power (VCDP) with interval number. Finally, a day-ahead optimal interval scheduling model for the PV-BES considering VES is formulated, aiming at to minimize the electricity energy purchase cost of the PV-BES from the external grid. Numerical simulation is conduced and the results validated the effectiveness of the proposed method.